Nitrogen content diagnosis of apple trees canopies using hyperspectral reflectance combined with PLS variable extraction and extreme learning machine - Chen, Shaomin; Ma, Lihui; Hu, Tiantian; Luo, Lihua; He, Qiong; Zhang, Shaowu (International Journal of Agricultural and Biological Engineering, 2021)
Nitrogen (N) is an important mineral element in apple production. Rapid estimation of apple tree N status is helpful for achieving precise N management. The objective of this work was to explore partial least squares (PLS) regression in dimensional reduction of spectral data and build the diagnostic model. The spectral reflectance data were collected from Fuji apple trees with 4 levels of N fertilizer treatment in the Loess Plateau in 2018 and 2019 using an ASD portable spectroradiometer, and leaf total N content was obtained at the same time. The raw spectra were pretreated using Savitzky-Golay (SG) smoothing and a combination of SG and first-order derivative (SG_FD) or second-order derivative (SG_SD). The samples were divided into a calibration dataset and a prediction dataset using SPXY. Based on 4 factors of PLS regression, including latent variables (LVs), X-loading, variable importance in projection (VIP) and regression coefficients (RC), the 6 methods (LVs, X-loading, VIP_01, VIP_02, RC_01 and RC_02) were derived and used for variable extraction, based on which PLS model and ELM model were established. The results indicated that the spectral data processed by SG_FD had the highest signal-to-noise ratio and was selected for subsequent analysis. The amounts of variables extracted by LVs, X-loading, VIP_01, VIP_02, RC_01 and RC_02 were 6, 11, 18, 305, 26 and 88, respectively. The method of extracting variables with an RC threshold based on the minimum RMSEP (RC_02) could effectively avoid the omission of effective information. The RC_02 method was recommended for related research which required accurate wavelength information as a variable. The variable extraction method based on LVs generated an ELM model with a simple structure. The prediction results showed that the ELM model outperformed the PLS model. The PLS(LVs)_ELM model was the best; R2P, RMSEP and RPD were 0.837, 2.393 and 2.220, respectively. Keywords: partial least square, variable extraction method, extreme learning machine, hyperspectral reflectance, apple tree, canopy nitrogen content DOI: 10.25165/j.ijabe.20211403.6157 Citation: Chen S M, Ma L H, Hu T T, Luo L H, He Q, Zhang S W. Nitrogen content diagnosis of apple trees canopies using hyperspectral reflectance combined with PLS variable extraction and extreme learning machine. Int J Agric & Biol Eng, 2021; 14(3): 181–188.